Monitoring follicular dynamics to determine estrus type and timing of ovulation induction in captive brown bears (Ursus arctos) - Yoshiko TORII; Naoya MATSUMOTO; Hideyuki SAKAMOTO; Masashi NAGANO; Seiji KATAGIRI; Yojiro YANAGAWA (The Society for Reproduction and Development, 2020)
It is important to understand ovarian physiology when developing an artificial insemination (AI) protocol. Brown bears (Ursus arctos) have a breeding season from May to July, although the type of estrus (polyestrus or monoestrus) is still contested. The present study aimed to define the ovarian dynamics, including follicular waves and ovulatory follicle size, and estrus type in brown bears. Six brown bears were used for ovarian ultrasonography; four were observed between April and October (before the start and after the end of the breeding season) and two in June (breeding season). In addition, we attempted to induce ovulation by administering a gonadotropin releasing hormone (GnRH) agonist. We observed follicular development in April in four bears, but follicles did not develop to greater than 6.0 mm in diameter until May. Thereafter, a group of follicles developed to more than 6.0 mm and grew as dominant follicles, except in one bear. After ovulation and subsequent corpus luteum (CL) formation, the follicular waves disappeared. Furthermore, in three bears treated with GnRH, follicles between 8.2 to 11.2 mm in diameter at the time of treatment ovulated and formed CLs. In two bears, follicles between 5.8 to 8.8 mm ovulated spontaneously within the observation interval. Our results suggest that brown bears may be monoestrous animals. Therefore, AI can only be performed once during the breeding season. Our results also suggest that dominant follicles larger than 8.0 mm are a suitable size for inducing ovulation.